Dehydrogenation of dimethylamine-borane mediated by Group 1 pincer complexes - Nolla-Saltiel, Roberto; Geer, Ana M; Lewis, William; Blake, Alexander J.; Kays, Deborah L. (Royal Society of Chemistry, 2018)
Group 1 salts containing carbazolido NNN pincer ligands are precatalysts for the dehydrogenation of Me2NH·BH3. NMR monitoring and DOSY studies show a heavy dependence on the metal and solvent, allowing in some cases selective formation of dehydrogenation products consistent with hydrogen liberation.